GENERATE KUNCI SHA1, MD5, SHA-256 PADA JAVA ANDROID STUDIO - Viving Frendiana; Fitri Elvira Ananda (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Data security issues are a very serious problem in the use of information systems. Almost all the data we use is stored in a database that can be accessed online and can be used by any user. Data security can be done in several ways, for example limiting access rights and applying cryptographic methods. Hash algorithm, which is also called message digest algorithm is used to generate a special message digest for random messages. Secure Hash Algorithm (SHA) is a Hash function that is "irreversible" into the original message (one way) which will produce a checksum or fingerprint of the data. The Hash functions used for this research are SHA1, MD5, and SHA-256. On the other hand, accessing and retrieving information in this digital era is getting easier and faster. This development can also affect the way someone carries out the identity verification process to enter a system. The identity verification process that is widely used is using a fingerprint detection tool. It is hoped that Generating SHA1, MD5, SHA-256 Keys and Fingerprint Login Authentication in Java Android Studio Chipmunk can become a basic step in developing login security in the future.